Prospecção de moléculas bioativas sintetizadas por bactérias do trato intestinal de crustáceos - Soares, Raquel Cavalcante (2022)
Infectious diseases caused by bacterial pathogens are one of the main health problems in the clinical and animal fields. This is linked to the loss of effectiveness of antibiotics. In aquaculture, an alternative to these are probiotics, efficient in increasing the resistance of farmed animals to pathogens. The selection of probiotic strains is based on the screening of strains that produce inhibitory compounds against pathogens, with the genus Bacillus being a highlight, representing an excellent source for studies that seek new therapeutic compounds. The present work aimed to detect antibacterial activity in lipopeptide secondary metabolites of bacterial cultures that are part of the collection of microbial cultures Profa. Regine Vieira and which were isolated from the gastrointestinal tract of crustaceans. The strains used in the research were selected following the criteria of: origin and antagonistic activity to Vibrio harveyi. After checking the selection criteria, extracts free of bacterial cells (metabolic liquid) were prepared, which were evaluated for bacterial activity by diffusion in wells against Vibrio harveyi ATCC 14126 and Vibrio parahaemolyticus IOC 18950. Positive results were used to obtain lipopeptide extracts, which were subjected to thin layer chromatography using silica gel plates to promote the separation of compounds present in the extracts. Soon after, the plates were evaluated for antibacterial activity using the bioautography technique. Lipopeptide extracts with detected antibacterial activity were evaluated for resistance to temperatures of 45°C and 100°C and exposure to the proteinase K enzyme. The lipopeptide portion of most of the strains used was efficient against the pathogens evaluated in the bioautography technique and showed stability thermal and optimal performance after exposure to proteinase K. These may be suitable for use in aquaculture, added to feed, after an approach to characterization and extraction of bioactive substances. The results are promising as indicators of the discovery potential of new antimicrobial compounds with wide technological application among the microbiota of the intestinal tract of aquatic animals.